1895 Neb. Laws 209-10 - (:unkn) unknown (My University, 1895)
Art. 16, § 1: Prohibited the concealed carry of any pistol, revolver, dirk, Bowie-knife, billy, sling-shot, metal knuckles, or other dangerous or deadly weapons.
Keywords: CARRY - CONCEALED